Oryzalin-induced polyploidy in Vanda limbata (Blume): Phenotypic assessment - Murni Dwiati; Wahyu Nur Hasam; Agus Hery Susanto (Acta Biochimica Indonesiana)
Background: Vanda limbata is a natural orchid species found on Java Island, commonly known as V. limbata 'Jawa.' Enhancing plant vigor is essential to increase its potential as an ornamental plant, with one promising approach being induced polyploidy using chemical mutagens such as oryzalin.